Fighting HIV-1 Persistence: At the Crossroads of “Shoc-K and B-Lock” - Chiara Acchioni (MDPI AG, 2021)
Despite the success of highly active antiretroviral therapy (HAART), integrated HIV-1 proviral DNA cannot be eradicated from an infected individual. HAART is not able to eliminate latently infected cells that remain invisible to the immune system. Viral sanctuaries in specific tissues and immune-privileged sites may cause residual viral replication that contributes to HIV-1 persistence. The “Shock or Kick, and Kill” approach uses latency reversing agents (LRAs) in the presence of HAART, followed by cell-killing due to viral cytopathic effects and immune-mediated clearance. Different LRAs may be required for the in vivo reactivation of HIV-1 in different CD4+ T cell reservoirs, leading to the activation of cellular transcription factors acting on the integrated proviral HIV-1 LTR. An important requirement for LRA drugs is the reactivation of viral transcription and replication without causing a generalized immune activation. Toll-like receptors, RIG-I like receptors, and STING agonists have emerged recently as a new class of LRAs that augment selective apoptosis in reactivated T lymphocytes. The challenge is to extend in vitro observations to HIV-1 positive patients. Further studies are also needed to overcome the mechanisms that protect latently infected cells from reactivation and/or elimination by the immune system. The Block and Lock alternative strategy aims at using latency promoting/inducing agents (LPAs/LIAs) to block the ability of latent proviruses to reactivate transcription in order to achieve a long term lock down of potential residual virus replication. The Shock and Kill and the Block and Lock approaches may not be only alternative to each other, but, if combined together (one after the other), or given all at once [namely “Shoc-K(kill) and B(block)-Lock”], they may represent a better approach to a functional cure.